Factors Affecting Vascular Complications in Patients with Diabetes Mellitus: A Literature Review - Widaningsih, Ida; Ibrahim, Kusman; Nursiswati, Nursiswati (Media Publikasi Cendekia Indonesia, 2025)
Vascular complications in patients with diabetes mellitus (DM) are a major cause of morbidity and mortality, presenting a considerable impact on quality of life and global health burden. Although diabetes management continues to improve, vascular complications remain a major challenge. It is important to understand the factors that influence these complications to support more effective prevention and management. To explore the factors influencing vascular complications in patients with DM. This study used a literature review method. Articles were searched through three major databases, namely CINAHL, PubMed, and Scopus, using keywords such as